Sufism Reason in Islamic Education - Nasaruddin Umar; Made Saihu (Randwick International of Education and Linguistics Science Journal, 2022)
This paper discusses Sufism reasoning in Islamic education which is based on the meaning of ihsan as the basis for character building, referring to the Al-Quran as the main source of guidance for Muslims. Sophistication of ihsan as an approach, presupposes a close relationship between the heart and psychology. Through the intellectual approach, it can develop personality, and mental health that can increase piety, laughter, sincerity, gratitude, and other good deeds. This literature study confirms that ihsan as an educational approach is not only based on rewards and punishments, but rather based everything. His activities on love and affection. Although ihsan is understood as a means of getting closer to God in the world of Sufism, but to some degree ihsan can be a practical approach in the world. Character education. Here Ihsan can become a model of Islamic psychotherapy useful for preventation, curation, and mental rehabilitation, such as stress, traumatic, psychosis, psychoneurosis, frustration, and depression with love as the main foundation. Educators must instill an understanding of love and love to students through an ihsan approach, because without it, no matter how sophisticated the educational approach is. Used unsuccessfully. Therefore, ihsan can be one of the approaches in character education that teaches learners about love and love. A perspective that sits love as a symbol of communication and interaction between each other.